Strategi Komunikasi Persuasif Pada Episode 'Bangkit Dari Kegagalan' Kanal Youtube Satu Persen - Fitri Awliyani; Zuhriah (STAI Bumi Silampari, 2026)
The development of information technology has transformed YouTube into an educational digital space, one of which is through the One Percent channel which consistently produces self-development content. This study aims to comprehensively analyze the structure of persuasive message construction and identify the integration of Aristotle's rhetorical elements in a video entitled